Hello Sunday Morning: Strategies used to support temporary alcohol abstinence through participation in an online health promotion program. (28th December 2017) - Pennay, Amy; MacLean, Sarah; Rankin, Georgia; O'Rourke, Sean
Abstract: Issue addressed: Hello Sunday Morning (HSM) is an online program that encourages people to commit to a period of non‐drinking and blog about their experiences. Among a sample of Victorian HSM users, we aimed to explore the barriers faced and the strategies adopted to maximise potential for achieving temporary abstinence. Methods: A content analysis of blog data from 154 HSM users (a total of 2844 blog posts) was undertaken by three researchers. Participants were predominantly women aged 30‐50 years. Results: The most common barriers to achieving temporary alcohol abstinence reported by participants were stress and tiredness, pervasiveness of drinking in social life, negative effects from not drinking and negative reactions from others. The strategies most commonly implemented included drawing on HSM and other non‐drinking networks, self‐talk, engaging in non‐alcohol‐related activities and substituting alcohol with other drinks. Conclusions: Although significant individual and systemic barriers to abstaining from alcohol were identified by HSM users, multiple strategies were identified and effectively utilised to overcome these barriers. So what?: We suggest that the virtual support from an online community with a shared interest in reducing their alcohol use appears to be a useful health promotion strategy for temporarily reducing consumption, particularly for women.